What can be learned from the Covid-19 pandemic? A case study at Skaraborg Hospital Group - Plantin, Filippa; Sjöholm, Annie (My University, 2022)
Healthcare is a complex system and Swedish healthcare is struggling with capacity. During the Covid-19 pandemic starting in 2020, the healthcare system was put under enormous stress and capacity became an even more crucial aspect. The Covid-19 pandemic came with damaging consequences, and healthcare was forced to adapt to the circumstances. One area that received more attention was how production planning and control were conducted at the hospitals in Sweden. It is important to not lose this opportunity to learn from such a transformative event. This study investigates the learning from how the three hierarchical planning levels at a Swedish hospital managed the pandemic and how these learnings can improve the production planning and control processes at the hospital after the pandemic. A Case study was done, data was collected during 20 interviews with managers at the hospital and a questionnaire was sent out to all managers at the hospital. With an abductive research approach, iteration of data, theory, and analysis was needed and the ability to modify and make changes to the theory was possible. Concluding, the findings of the study showed proof of the crucial role of having a holistic perspective when conducting production plans. The study also identified the need for clarification of roles and mandates to improve the structure of the planning process. The implementation of planning levels should be further investigated. Wellfunctioning information flow and collaboration enhanced understanding and enabled collaborative planning. These learnings and their contribution to the hospital after the Covid-19 pandemic can improve the Production Planning and Control at the Swedish hospital to increase capacity utilization.
Keywords: Swedish healthcare, planning in Swedish healthcare, Production Planning and Control, PPC, hierarchical planning levels, Covid-19, pandemic